Structural, Functional and Inhibitory Annotations of Lumpy Skin Disease Virus Hypothetical Protein LSDV004: An In‐Silico Study - F. M. Yasir Hasib; Md. Shafiqul Islam (Veterinary Medicine and Science)
ABSTRACT Lumpy skin disease virus (LSDV) is the etiological agent of lumpy skin disease (LSD), predominantly afflicting cattle populations and posing significant economic implications to the livestock industry. Despite the comprehensive genome sequencing of LSDV, several hypothetical genes with unknown functions remain, potentially playing pivotal roles in disease pathogenesis and serving as targets for drug discovery. This study aimed to explore the LSDV004 gene by predicting its key properties, structure, functions and potential inhibitors using bioinformatic tools. Physiochemical analysis using ExPASy ProtParam indicates LSDV004 is a stable protein with an instability index below 40, suggesting structural stability. Secondary structure analysis via SOPMA identifies the random coil as the predominant structural element, covering 50.88% of residues, followed by extended strands (36.84%). The tertiary structure predicted and refined using SWISS‐MODEL and GalaxyRefine respectively, > 90% of residues in the favoured region of the Ramachandran plot, according to PROCHECK validation. Functional prediction highlights structural similarities with the Swinepox virus C2 and suggests potential involvement in pathways such as negative regulation of gene expression, as indicated by gene ontology (GO) analysis using I‐TASSER. Moreover, the GO analysis indicates functional similarity with anti‐apoptotic protein Bcl‐2‐like protein 1 (PDB ID: 1LXL). Molecular docking studies with HDOCK reveal pelcitoclax as exhibiting better docking characteristics compared to other Bcl‐2 inhibitors. However, it's important to note that these predictions require validation through wet laboratory experiments to confirm the LSV004 protein's structural, functional and inhibitory properties. These findings suggest LSDV004's role in LSD pathogenesis and its potential as a drug target and also highlight areas for further experimental studies to confirm its function, supporting efforts toward effective treatments and control.